1983
DOI: 10.1042/cs0650071
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Steroid Enzymes, Aromatase and 5α-Reductase in the Pancreas: A Comparison of Normal Adult, Foetal and Malignant Tissue

Abstract: 1. Following the finding of high levels of oestrogen receptor proteins in pancreatic carcinoma tissue, two enzymes involved in sex-steroid biosynthetic pathways, aromatase and 5 alpha-reductase, have been measured. 2. Activities of aromatase, which converts testosterone into oestradiol, comparable with those found in pre-menopausal uterus (P less than 0.5) were found in all seven samples of pancreatic carcinoma tissue, and in a pooled sample of foetal pancreas. Measurable but significantly lower activities (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 7 publications
3
20
0
Order By: Relevance
“…Somatostatin has been shown to suppress exocrine pancreatic secretion in rats, dogs and humans (11,12,14,18 (34) and found that testosterone levels were significantly reduced in patients with pancreatic carcinoma when compared to controls, possibly due to the uptake and metabolism within the tumor (34,35). The findings that pancreatic adenocarcinomas might be sex steroid dependent are supported by evidence from xenografts of human pancreatic adenocarcinomas in nude mice (36).…”
supporting
confidence: 69%
“…Somatostatin has been shown to suppress exocrine pancreatic secretion in rats, dogs and humans (11,12,14,18 (34) and found that testosterone levels were significantly reduced in patients with pancreatic carcinoma when compared to controls, possibly due to the uptake and metabolism within the tumor (34,35). The findings that pancreatic adenocarcinomas might be sex steroid dependent are supported by evidence from xenografts of human pancreatic adenocarcinomas in nude mice (36).…”
supporting
confidence: 69%
“…Moreover, in comparison with patients showing gastrointestinal tumours other than those of the pancreas and patients without malignancies, pancreatic-cancer patients exhibited significantly lower testosterone serum levels, which have been ascribed to interaction of testosterone with specific receptors on pancreatic-tumour cells (Fernandez del Castillo et af., 1990). Furthermore, significantly higher activity of aromatase and Sa-reductase have been found in pancreatic turnours in comparison with normal pancreas (Iqbal et al, 1983).…”
mentioning
confidence: 98%
“…The average survival is 6 months with an overall 5-year survival rate of less than 1% [2], Most of the reports evaluating treatment with cytotoxic drugs and/or radiation did not show any improvement in survival [3], Following the sug gestion by Greenway et al [4], a series of reports [5][6][7][8] have investigated estrogen receptor activity, estradiol binding proteins and growth response to estrogens and anti estrogens in different pancreatic cell lines. In 1983,Iqbalet al [9] found sex-steroid biosynthetic enzymes (aromatase and reductase) in pancreatic cancer tissue, while, in 1986, Corbishley et al [10] demonstrated androgen receptors in pancreatic cells, including human cancer cells. More re cently, a derangement in the serum androgen profile has been reported [11,12] with the suggestion that the testos terone concentration is significantly lower in patients with pancreatic cancer, while the level of androstenedione is higher, due to an increased uptake and metabolism by the tumourcells.…”
Section: Introductionmentioning
confidence: 99%